Application of Regional Climate Models in Assessing Climate Change Impact on Forest of Kanha Tiger Reserve - Devi, Rinku Moni; Sinha, Bhaskar; Dimri, A. P.; Saran, Sameer (Indian Forester, 2017)
The current paper attempts to understand the possible impacts of climate change on the forest of Kanha Tiger Reserve, Madhya Pradesh using different climate models and remote sensing techniques. The aim of the study was to assess the response of natural vegetation to climate drivers. Different sources of climate data over a time period of 33 years and satellite images of the different time period were used for the study. Normalised Difference Vegetation Index (NDVI) and climate variables (rainfall and temperature) were analyzed for detecting the change in vegetation. The change in vegetation was correlated with change in variability of precipitation and temperature. The results showed that on an average there is variation in the vegetation status with the change in climate variables. Further, it can be recommended that integrating regional climate models and remote sensing techniques can better help in understanding the present and future impacts of climate change on forest ecosystems and can contribute in planning effective adaptation strategies in the forestry sector.